2018
DOI: 10.1088/2058-6272/aad9f1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on the jet characteristics of a steam plasma torch

Abstract: Thermal steam plasma jet is promising for applications in environmental industries due to its distinctive characteristics of high enthalpy and high chemical reactivity. However, the performance of the steam plasma torch for its generation is limited by the problems of the large arc voltage fluctuation and serious erosion of the electrodes. In this study, a gas-stabilized steam plasma torch which can operate continuously and stably was designed. Experiments were conducted to reveal the effect of the different w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The increase of the gas flow rate compresses the arc column more strongly, which leads to an increase of the thickness of the cold boundary layer. The increased thickness of the cold boundary layer reduces the heat loss conducted to the wall of the arc chamber [56]. The heat loss transferred from the gas to the arc chamber wall should decrease as the gas flow rate increases.…”
Section: Heat Loss In the Arc Chambermentioning
confidence: 99%
“…The increase of the gas flow rate compresses the arc column more strongly, which leads to an increase of the thickness of the cold boundary layer. The increased thickness of the cold boundary layer reduces the heat loss conducted to the wall of the arc chamber [56]. The heat loss transferred from the gas to the arc chamber wall should decrease as the gas flow rate increases.…”
Section: Heat Loss In the Arc Chambermentioning
confidence: 99%
“…A large number of numerical modelings [22,[26][27][28][29] and experimental studies [30][31][32][33][34] have been performed to analyze the mechanisms of anode erosion, and propose the methods to inhibit the anode erosion. The modeling found that the arc usually attached on the anode surface in the diffusive or constricted forms.…”
Section: Introductionmentioning
confidence: 99%